Exploring The Relation Between Learning Style and Learning Outcome in Basic Level of Nihongo Course - Prasetyo, Joko; Soepardjo, Djodjok; Pratita, Ina Ika; Nurhadi, Didik; Amri, Miftachul (Universitas Cokroaminoto Palopo, 2024)
Grammar is is an integral part of language competencies that must be mastered by foreign language learner, as one of the requirements for mastering all of language competencies. Therefore various strategies are being attempted in order to help students gain the learning outcomes of the course. In learning activities, it was found that students who were identified as a group with lower initial abilities were able to achieve high learning outcomes at the end of the semester. The students' learning styles are assumed to have a contribution to the students learning outcomes, because students have learn with the same learning resources, and the methods used by teachers are not different. This became the starting point to explore the relationship between learning styles and student learning outcomes. This research is a quantitative research to describe the correlation between learning styles and student learning outcomes in the basic level of Nihongo subject. This study will also describe the quality of the relationship between the two variables. The population in this study is all undergraduate students of State University of Surabaya (UNESA) Japanese Language Education Program class of 2022, totaling 104 students. The sampling method used in this study is a non-sampling method because all members in one population will be the subject of this study. Based on the results of the analysis that has been done, the following conclusions can be drawn: 1) The learning styles of UNESA Japanese Language Education Program students class of 2022 were analyzed based on VARK model learning style preferences, showing that students have a single learning style and a combined learning style. However, The most dominant learning style preference used by students is Kinesthetic learning style with more than half of the total number of respondents. In addition, gender-based learning style preferences show that female student groups have a greater number of combined learning styles than male student groups; 2) The correlation between students' learning styles, and Japanese learning outcomes after being analyzed through a non-parametric model showed that the coefficient value of both variables of this study is 0.663, which is classified as